Preventing immediate‐onset food allergy in infants, children and adults: Systematic review protocol. Issue 3 (13th December 2019) - de Silva, Debra; Halken, Susanne; Singh, Chris; Muraro, Antonella; Angier, Elizabeth; Arasi, Stefania; Arshad, Hasan; Beyer, Kirsten; Boyle, Robert; Eigenmann, Philippe; Grimshaw, Kate; Hoest, Arne; et al.
Abstract: Background: More than 17 million people across Europe have allergies to food and the burden of food allergies is increasing. In 2014, the European Academy of Allergy and Clinical Immunology (EAACI) published guidelines for preventing food allergy. Important research has been published since then and it is essential to ensure the guidelines reflect the latest evidence. A systematic review will be undertaken to help prepare new guidelines due to be published in 2020. Methods: Eleven bibliographic databases will be searched from inception to 31 October 2019 for randomized controlled trials about any intervention designed to prevent the development of new cases of immediate‐type/IgE‐mediated food allergy in infants, children and adults. There are few randomized controlled trials about the impact of breastfeeding on food allergy so prospective cohort studies about breastfeeding with at least 1000 participants at general risk or 200 at high risk of food allergy will also be eligible. The Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach will be used to assess the certainty of the evidence and tabulate summary data. The risk of bias in individual trials will be assessed using the Cochrane risk of bias tool. All data extraction and quality appraisal will be undertaken independently by two reviewers in partnership with a taskforce of EAACI members. Conclusions: Preventing food allergy has the potential to improve personal well‐being and reduce societal healthcare costs. It is important that forthcoming European guidelines take the latest research into account. Past reviews have tended to focus on single interventions or combined food allergy with other outcomes, making it difficult to draw robust conclusions about potential impacts for policy and practice.